The Influence of Intention to use Medians Potato Varieties on the Result of Technological Innovation Development with Technology Acceptance Models - Ujang Sumarwan,, Muhammad .H. Rasyidha, Mukhamad Najib, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this study was to analyze the intention of farmers to use the potato varieties of medians with the development of technology acceptance models (TAM) that combine innovation diffusion theory, subjective norms, self-efficacy, and facilitate conditions to determine the intentions of farmers to use. The method used was a survey with face-to-face interviews with 120 potato farmers. Sampling was taken based on non-probability sampling using convenience sampling techniques. Analysis of the data used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results show that variables triability, perceived usefulness, subjective norms, and compatibility directly have a positive effect on the intention to use potato varieties medians. While the variables that can be observed, perceived ease of use, perceived self-efficacy, and facilitating conditions do not have a positive effect on the intention to use.